Evaluation Of Indicators Of Neutrophilic Link Of Phagocytosis In Patients With Chronic Forms Of Rhinosinusitis After Endoscopic Operations (Eurasian Medical Research Periodical, 2024)
In recent years, there has been a significant increase in chronic rhinosinusitis (CRS) in the structure of diseases of the ENT organs. Chronic forms of rhinosinusitis are one of the most common and often recurrent diseases of the nose and paranasal sinuses, the nature and mechanism of which have not been fully understood. The aim of this work is to study the main indicators of the neutrophilic link in phagocytosis in patients with chronic forms of rhinosinusitis. After the operative period, all patients underwent endonasal lowintensity laser therapy and recovery was observed in all patients. In conclusion, it should be noted that the use of endonasal low-intensity laser therapy after surgical treatment has shown some effective results compared with traditional treatment.